Pengaruh penggunaan Norplant terhadap kadar T3,T4 dan TSH pada akseptor di daerah endemik gondok - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
Zainal Arifin Nang Agus â Influence of Norplant on T3, T4 and TSH concentration in acceptor in endemic goiter area. Norplant contains a potent progesteron, namely levonorgestrel. It induces iodine excretion in urine and simultaneously stimulates the thyroid function. The objectives of this study were to examine the T3, T4 and TSH concentration of the Norplant acceptors for 3 months. The subjects were 8 acceptors of Norplant taken from an endemic goiter area in Cangkringan, Sleman, Yogyakarta. The results of this study showed that T3, T4 and TSH were in normal range but they were in the low level. Three months after using Norplant, T3 and T4 level increased, but they are not significant (p>0,05). On the other hand, T4 level decreased significantly (p